Early real-world outcomes of intravitreal aflibercept 8 mg in treatment-Naïve neovascular AMD: AI-assisted fluid volume analysis - Jennifer Cattaneo; Eva C. De Oliveira Figueiredo; Andrea Montesel; Sandra Vermeirsch; Chiara M. Eandi (International Journal of Retina and Vitreous)
Abstract Background This study was conducted as a retrospective, exploratory analysis to assess early anatomical and functional effects of intravitreal aflibercept 8 mg in neovascular age-related macular degeneration (nAMD) in a small cohort of patients. Methods This retrospective study was conducted at the Jules Gonin Eye Hospital in Lausanne, Switzerland, and included treatment-naïve patients with nAMD. Patients received a minimum of two intravitreal injections (IVT) of aflibercept 8 mg over a 3-month period. Key outcomes assessed were changes in best-corrected visual acuity (BCVA), central subfield thickness (CST), mean retinal thickness (RT), total fluid (TF) volume which was calculated as the sum of intraretinal fluid (IRF), subretinal fluid (SRF) and pigment epithelial detachment (PED) volumes. These parameters were evaluated at baseline, month 1, and month 3 using the RetinAI Discovery® platform, an artificial intelligence-based analysis system. Results 10 eyes of 10 patients were enrolled. Mean age was 77.7 ± 12.5 years. Comparative analysis between baseline, month 1, and month 3 revealed statistically significant reduction in CST, RT and TF volume, indicating a positive early response to treatment. One adverse event of intraocular inflammation (IOI) occurred in one patient (10%) after the second IVT injection. Treatment was subsequently interrupted, and IOI resolved with topical corticosteroids therapy. Conclusion Intravitreal aflibercept 8 mg demonstrated early anatomical and functional improvements in nAMD treatment-naïve patients after the first 3-months. The use of the AI-based analysis allowed for detailed and automated assessment of retinal changes, providing valuable insights into early treatment effects. Given the retrospective design and small cohort, further studies are warranted to assess long-term outcomes and the potential predictive value of early changes on long-term visual prognosis and safety. Clinical trial number Not applicable.